Índice de violencia de género en Ecuador durante la pandemia - Erazo-Marín, Federico Eduardo; Lemos-Espinoza, Aura Marina; Coronel-Piloso, Johanna Emperatriz; Peñaherrera-Martínez, Elba Tatiana (IUSTITIA SOCIALIS, 2022)
Índice de violencia de género en Ecuador durante la pandemia